The Influence of Health Education Using Leaflets and Flashbacks on Patient Knowledge about Gastritis - Latupapua, Valenchia Geraldyne; Anggraini, Rima Berti; Hermain, Hermain (Inspirasi Foundation, 2025)
Introduction: Gastritis, or what we commonly know as stomach ulcers, is the beginning of a disease that can disrupt a person's quality of life. According to WHO data, the incidence of gastritis in Indonesia is 40.8%. This is due to a lack of public awareness about gastritis. Objective: This study aims to determine the effect of health education using leaflets and flipcharts on patient knowledge about gastritis. Method: The study used a quasi-experimental design with a two-group pretest and posttest. The sample size was 82 patients. Quota sampling was used as the sampling technique. The instruments used were leaflets, flipcharts, and questionnaires. Data were analyzed using a paired sample t-test and an independent t-test with a 95% confidence level (α 0.05). Result: The results of the study indicate that health education using leaflets and flipcharts has an effect on patient knowledge about gastritis. The results of each study using leaflets and flipcharts obtained a p-value of (0.000) < ɑ (0.05). This data was also analyzed using a T-test of different variants, which showed a difference in the average level of patient knowledge after receiving health education about gastritis using leaflets and flipcharts. Judging from the average score of patient knowledge using leaflets and flipcharts, health education using flipcharts proved more effective in increasing patient knowledge about gastritis. The recommendation from this study is the need to increase awareness and commitment to providing information about gastritis, preferably using flipcharts and leaflets. Conclusion: The suggestion from this research is the need to increase awareness and commitment to be willing to provide information about gastritis, preferably using flipchart media and also through leaflets.